Protecting the world's finest athletes: periodic health evaluation practices of the top performing National Olympic Committees from the 2016 Rio or 2018 PyeongChang Olympic Games. Issue 17 (19th January 2021) - Nabhan, Dustin; Taylor, David; Lewis, Melie; Bahr, Roald
Abstract : Aim: To describe the periodic health evaluation (PHE) practices of the top performing National Olympic Committees (NOCs). Methods: We sent a survey to NOCs finishing in the top 8 for medal count at the 2016 Rio Olympic Games or 2018 PyeongChang Olympic Games. The survey included four sections: (1) PHE staff composition and roles, (2) beliefs regarding the PHE, (3) a ranking of risk factors for future injury and (4) details on the elements of the PHE. Results: All 14 NOCs with top 8 finishes at the 2016 Rio Olympic Games or 2018 PyeongChang Olympic Games completed the survey. NOCs included a median of seven staff specialties in the PHE, with physicians and physiotherapists having the highest level of involvement. There was agreement that PHEs are effective in identifying current health conditions (13/14) and that athletes should receive individualised action plans after their PHE (14/14), but less agreement (6/14) that PHEs can predict future injury. The practices of NOCs were diverse and often specific to the athlete population being tested, but always included the patient's health history, laboratory studies, cardiovascular screening and assessments of movement capacity. The top three risk factors for future injury were thought to be previous injury, age and training experience. Conclusions: Among the top performing NOCs, the PHE is a comprehensive, multidisciplinary process aimed to identify existing conditions and provide baseline health and performance profiles in the event of future injury. Research linking PHEs to injury prevention is needed.